Desakralisasi Upacara 17 Agustus di Istana Merdeka Pada Masa Pemerintahan Joko Widodo: dalam Tinjauan Analisis Wacana Kritis - Novalia Novalia; Rindana Intan Emeilia; Arina Muntazah (Prisani Cendekia Institute, 2022)
This study aimed to describe the text dimensions of the news on the 77th Indonesian Independence Day Commemoration Ceremony in the Kompas.com newspaper with the headline